POLA MANAJEMEN BIMBINGAN DAN KONSELING ISLAMI DI MAN - ACEH BESAR - Hadini, Hadini; Imamuddin, M.; Masbur, Masbur; Hayati, Hayati; M., Zaharuddin (re-JIEM (Research Journal of Islamic Education Management), 2025)
The role of management in Guidance and Counseling institutions is absolutely necessary. In various Islamic educational institutions, it seems that not all of them have paid attention to the management of Guidance and Counseling, this is as seen from the results of researchers' observations at the MAN 4 Aceh Besar Educational institution, where it appears that although it has had a Guidance and Counseling institution and organization, it has not fully implemented and carried out the management function correctly. Based on these problems, the researcher is interested in exploring more deeply about how the pattern of implementation of Guidance and Counseling management in the institution. The research method used is descriptive analysis research with a qualitative approach. Data collection techniques with interviews, observation and documentation. the study it was found that MAN 4 Aceh Besar has implemented management functions in the form of planning, organizing, actuating and controlling, but it appears that the implementation of these functions has not been optimal. However, there are some peculiarities in practice, such as appreciation, deliberation, mutual help, silaturrahmi, and so on. The benefit this research is have an alternative to practice in management counselling in Madrasah.